Innovative use of SMART Cable Bolt Data: Numerical - Back Analysis for Interpretation of Post Failure Rock Mass Properties Post- - Jason J. Crowder (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
Presentation Outline ? Introduction ? Costs of ground support and rehabilitation ? Why post-failure rock mass properties are necessary ? The Rock Mechanics Problem ? Present State of Modelling and Instrumentation in Mining ? Case Study Background ??Williams Mine ? Deriving Parameters for Modelling from Instrumentation ? Results from Case Study ??Back Analyses ? Discussion of Research Impact t Summary